Pengaruh Karakteristik Individu Dan Lingkungan Kerja Terhadap Disiplin Kerja Karyawan Pada Perumda Tirta Pakuan Kota Bogor (PDAM) PERIODE 2022-2023 - Ratu Fitri Chairunisa; Sigit Purwanto; Mohammad Jibriel Avessina (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to determine the influence of individual characteristics and the work environment on employee work discipline at PERUMDA Tirta Pakuan Bogor City (PDAM). The population in this study was all 449 employees of PERUMDA Tirta Pakuan Bogor City (PDAM). The method for determining the sample in this research was to use purposive sampling of 82 employees. The data used in this research is primary data. Data collection techniques include observation, interviews, questionnaires and literature study. The data analysis method used is quantitative data. Data testing used Multiple Linear Regression analysis with the help of SPSS 25. The research results showed that individual characteristic variables had a significant effect on work discipline variables. Work environment variables do not have a significant effect on work discipline variables. Individual characteristics and work environment variables have a significant effect on work discipline variables.